2022
DOI: 10.1093/jas/skac221
|View full text |Cite
|
Sign up to set email alerts
|

Acute stress deteriorates breast meat quality of Ross 308 broiler chickens by inducing redox imbalance and mitochondrial dysfunction

Abstract: This study investigated the effects of acute stress on breast meat quality, redox status and mitochondrial function in pectoralis major (PM) muscle of broilers. A total of 168 broiler chickens (42-day-old, Ross 308) were randomly divided into control (CON) and pre-slaughter transport (T) treatments. A broiler was an experimental unit. Each treatment consisted of 84 broilers, and they were put in 12 crates with 7 broilers each. Broilers in the T group were transported according to a designed protocol, and the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 47 publications
4
13
0
Order By: Relevance
“…Herein, we observed that pre-slaughter transport at high ambient temperature disturbed redox homeostasis and induced oxidative stress in the PM muscles of broilers by increasing ROS generation, lipid peroxidation, and protein oxidation. In addition, the adaptive responses of broilers to pre-slaughter transport stress were insufficient, as the activities of antioxidant enzymes, including T-AOC, T-SOD, and GSH-Px, remained unchanged, which is in accordance with the findings obtained by Liao et al [ 40 ]. HSP70 exerts its cytoprotective effect by facilitating the degradation of damaged oxidized proteins via the ubiquitin-proteasome system, as well as by inducing the expression of key antioxidant enzymes and adjusting their activities under oxidative stress [ 41 ].…”
Section: Discussionsupporting
confidence: 90%
“…Herein, we observed that pre-slaughter transport at high ambient temperature disturbed redox homeostasis and induced oxidative stress in the PM muscles of broilers by increasing ROS generation, lipid peroxidation, and protein oxidation. In addition, the adaptive responses of broilers to pre-slaughter transport stress were insufficient, as the activities of antioxidant enzymes, including T-AOC, T-SOD, and GSH-Px, remained unchanged, which is in accordance with the findings obtained by Liao et al [ 40 ]. HSP70 exerts its cytoprotective effect by facilitating the degradation of damaged oxidized proteins via the ubiquitin-proteasome system, as well as by inducing the expression of key antioxidant enzymes and adjusting their activities under oxidative stress [ 41 ].…”
Section: Discussionsupporting
confidence: 90%
“…These results suggested that acute stress might change the expression of calcium channels on the cell membrane, leading to the continuous entry of extracellular Ca 2+ and the abnormal outflow of Ca 2+ in the cytoplasm, thereby triggering cytoplasmic calcium overload. We recently demonstrated that the impact of acute stress on the mitochondria mainly occurred in the imbalance of the redox state and mitochondrial dysfunction . Herein, no significant effect of acute stress on mitochondrial Ca 2+ concentration and MCU mRNA expression and protein content was observed.…”
Section: Discussionmentioning
confidence: 80%
“…We recently demonstrated that the impact of acute stress on the mitochondria mainly occurred in the imbalance of the redox state and mitochondrial dysfunction. 19 Herein, no significant effect of acute stress on mitochondrial Ca 2+ concentration and MCU mRNA expression and protein content was observed. Although acute stress induced the increase of the cytoplasmic Ca 2+ concentration, mitochondrial MCU did not perceive this change as the threshold for its opening was about 1 μM.…”
Section: ■ Discussionmentioning
confidence: 81%
See 2 more Smart Citations